Systemic inflammation as a mediator in the link between obesity and depression: Evidence from a nationwide cohort study - Xiaoqing Wang; Xinyue Liang; Ming Jiang; Ling Wei; Xiangpeng Shi; Fang Fang; Jing Cang (BMC Psychiatry)
Abstract Background Obesity and depression are major public health issues with a complex, bidirectional relationship potentially involving systemic inflammation. Methods Using a diverse sample from the National Health and Nutrition Examination Survey (NHANES) (n = 11,324; weighted population = 456,457,366), we examined the associations between obesity, systemic inflammation, and depression. Obesity was classified by Body Mass Index (BMI), depressive symptoms were assessed with the Patient Health Questionnaire-9 (PHQ-9), and systemic inflammation was measured using markers like Neutrophil-to-Lymphocyte Ratio (NLR), Systemic Inflammation Response Index (SIRI), and Systemic Immune-Inflammation Index (SII). Weighted logistic regression models were used to assess relationships between obesity, inflammation, and depression. Linear regression evaluated BMI’s association with inflammation markers, and Restricted Cubic Spline (RCS) analysis explored their interrelationships. Subgroup analyses and interaction tests were conducted, and mediation analysis examined the role of inflammation markers in mediating the obesity-depression association. Results Class III obesity was associated with higher inflammatory marker levels and increased depression risk. Mediation analysis showed NLR, SIRI, and SII mediated 5.2%, 5.9%, and 6.1% of the obesity-depression relationship. Conclusions Systemic inflammation partially mediates the relationship between obesity and depression.